PELATIHAN INTERNET SEHAT: KEPEDULIAN DIRI AKAN KEAMANAN INFORMASI - Agung Sediyono; Is Mardianto; Muhammad Najih; Gatot Budi Santoso; Abdul Rochman (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
Internet and social media usage in daily activities is continuously increasing. UKM gets the benefit of information technology to increase its sale through scale up the marketing target in order to increase its revenue. However, most of UKM are worry about the risk in using information technology in their daily activities, such as cyber fraud and stealing their private data and their identities. To overcome these problems, it needs to design training materials that can reduce theirs worry in using information technology. Designed training material based on problem faced by training participants can satisfy and give a benefit to participants even though the instructor delivery and response is not good.